Antenatal diagnosis of chorioamnionitis: A review of the potential role of fetal and placental imaging. (17th June 2022) - Hall, Megan; Hutter, Jana; Suff, Natalie; Avena Zampieri, Carla; Tribe, Rachel M.; Shennan, Andrew; Rutherford, Mary; Story, Lisa
Abstract: Chorioamnionitis is present in up to 70% of spontaneous preterm births. It is defined as an acute inflammation of the chorion, with or without involvement of the amnion, and is evidence of a maternal immunological response to infection. A fetal inflammatory response can coexist and is diagnosed on placental histopathology postnatally. Fetal inflammatory response syndrome (FIRS) is associated with poorer fetal and neonatal outcomes. The only antenatal diagnostic test is amniocentesis which carries risks of miscarriage or preterm birth. Imaging of the fetal immune system, in particular the thymus and the spleen, and the placenta may give valuable information antenatally regarding the diagnosis of fetal inflammatory response. While ultrasound is largely limited to structural information, MRI can complement this with functional information that may provide insight into the metabolic activities of the fetal immune system and placenta. This review discusses fetal and placental imaging in pregnancies complicated by chorioamnionitis and their potential future use in achieving non‐invasive antenatal diagnosis. Key points: What's already known about the topic? Chorioamnionitis is present in up to 70% of spontaneous preterm births and is associated with more complications than unaffected spontaneous preterm births Diagnosis is postnatal. Antenatal diagnosis by amniocentesis carries a risk of preterm birth, and is not integrated into clinical care What does this review add? Ultrasound assessment of the fetal immune system gives structural information and limited functional information, while MRI can complement this with greater functional tissue information Imaging may play a role in the non‐invasive antenatal diagnosis of chorioamnionitis